Identification of amino acids controlling the low-pH-induced conformational change of rabies virus glycoprotein. - Gaudin, Y (1996)
The glycoprotein (G) of rabies virus assumes at least three different conformations: the native state detected at the viral surface above pH 7, the activated state involved in the first step of the fusion process, and the fusion-inactive conformation (I). A new category of monoclonal antibodies (MAbs) which recognized specifically the I conformation at the viral surface has recently been described. These MAbs (17A4 and 29EC2) became neutralizing when the virus was preincubated at acidic pH to induce the conformational change toward the I state of G. Mutants escaping neutralization were then selected. In this study, we have investigated the fusion and the low-pH-induced fusion inactivation properties of these mutants. All of these mutants have fusion properties similar to those of the CVS parental strain, but five mutants (E282K, M44I, M44V, V392G, and M396T) were considerably slowed in their conformational change leading to the I state. These mutants allow us to define regions that control this conformational change. These results also reinforce the idea that structural transition toward the I state is irrelevant to the fusion process. Other mutations in amino acids 10, 13, and 15 are probably located in the epitopes of selecting MAbs. Furthermore, in electron microscopy, we observed a hexagonal lattice of glycoproteins at the viral surface of mutants M44I and V392G as well as strong cooperativity in the conformational change toward the I state. This finding demonstrates the existence of lateral interactions between the spikes of a rhabdovirus.